Anti-Dll4 therapy: can we block tumour growth by increasing angiogenesis? - Sainson, R; Harris, A (2007)
Since the early 1970s, the dogma postulating that blocking tumour angiogenesis can inhibit tumour growth has been accepted widely and has resulted in the generation of a variety of successful anti-angiogenic therapies. More recently, new signalling pathways, such as the Dll4-Notch signalling pathway, have been shown to regulate angiogenesis during development. In pathological conditions, such as cancer, Dll4 is up-regulated strongly in the tumour vasculature. Based on this expression pattern, different molecules have been generated to block Dll4 signalling. Unexpectedly, these blocking agents inhibited tumour growth in vivo by triggering excessive but nonfunctional angiogenesis. Altogether, these molecules constitute a new category of pro-angiogenic yet anticancer agents and offer an exciting alternative to previously described vascular targeting molecules.